Interpersonal perceptions of personality traits in elite coach-athlete dyads - Stanford, J. R.; Healy, L. C.; Sarkar, M.; Johnston, J. P. (Psychology of Sport and Exercise, 2022)
Introduction: The extent to which coaches and athletes can effectively work together is an essential consideration in the pursuit of athletic success. This is particularly important at the elite level due to the high pressures on tangible outcomes, such as reaching the podium of a major competition. This study sought to explore and explain how both coaches and athletes identify personality traits in themselves and their partners to manage and maintain a positive relationship. Methods: Using a mixed methodological design underpinned by critical realism, four elite coach-athlete dyads (four male coaches, one male athlete, three female athletes) were purposefully recruited from a single sport. Each participant completed the 44-item Big Five Inventory (John & Srivastava, 1999) on their own and their partner`s perceived personality traits. The data generated were used to inform the discussions in follow-up, individual semi-structured interviews with all participants. Results: The interview data were analysed using thematic analysis, which generated three higher themes and seven lower order themes. The three higher order themes were perceived compatibility, relationship persona and collective personality. Conclusion: The present investigation has identified what coaches and athletes perceive to be the key personality characteristics to manage and maintain a successful working relationship.